Analisis Prokrastinasi Akademik Mahasiswa (Studi Pada Mahasiswa Program Studi Bimbingan Dan Konsling Islam Angkatan 2018 Di UIN Khas Jember) - Damayanti, Shelvya Putri; Anggraeni, Devita Safitri; Chisnulloh, Mukhammad; Fitriana, Ani Qotus Zuhro’ (CV. ITTC INDONESIA, 2023)
Academic procrastination is a tendency to delay doing and completing tasks in the academic field completely. Academic procrastination also occurs among students. This study aims to determine the existence of academic procrastination and the factors that cause academic procrastination in students of the Islamic guidance and counseling study program at Uin Jember, class of 2018. The research method used is a qualitative research method with interview techniques. The subjects of this study were 5 students of the Islamic Guidance and Counseling Study Program at Uin Jember, class of 2018. The results of this study were that there was academic procrastination in students of the Islamic Guidance and Counseling Study Program at Uin Jember, class of 2018 and it was also known that the factors causing academic procrastination in 2018 class students namely, feeling lazy, busy working, lack of facilities, repeating courses, taking special courses, it is difficult to determine the time of guidance due to clashes with other activities, among these factors the biggest factors are feeling lazy and busy working.